PEMANFAATAN LIMBAH KOTORAN SAPI SEBAGAI PENGGANTI SEBAGIAN SEMEN DALAM PEMBUATAN BATAKO - Kiki Kurniawan; Prihantono Prihantono; Rosmawita Saleh (Menara: Jurnal Teknik Sipil, 2020)
The results showed the use of cow dung waste can increase the compressive strength of hollow brick from any composition of waste. Hollow brick with cow dung substitution of 0% has an average compressive strength value 44.75 Kg/Cm2 has an average water absorption of 14.31%, hollow brick with cow dung substitution of 5% has a value of compressive strength average 47.47 Kg/Cm2 has an average water absorption of 15.67%, Batako perforation with cow dung substitution of 7.5% has an average compressive strength value of 51.83 Kg/Cm2 has the absorption water averaging 13.71%, batako perforated with substitution of cow dung waste of 10% has an average compressive strength value 53.81 Kg/Cm2 has an average water absorption of 10.04%, hollow brick with substitution cow dung waste of 12.5% has an average compressive strength value of 50.66 Kg/Cm2 has an average water absorption of 23.6%, hollow brick with cow dung substitution of 15% average 48.84 Kg/Cm2 has an average water absorption of 19.72%. The optimum compressive strength value was obtained from percentage substitution of cow dung waste at 10% with mean value of compressive strength 53,81 Kg/Cm2 with average water absorption 10,04%.